Technical analysis of the creation of a permanent establishment for a non-resident employer by virtue of its employees working remotely from another country - Landers, Megan Aasiyah (Department of Finance and Tax, 2026)
Remote working is certainly no new phenomenon; it has only become more prevalent because of the COVID-19 pandemic. Remote working became possible with the development of the telephone, internet, laptops and smart devices, and allows employees not to be confined to their employer's workplaces. It is widely understood that a state can only tax an enterprise if it has a PE in that state. Consequently, there is a need to examine whether a remote employee can establish a PE in a state and create a taxable presence for their employer in the host state. A PE may exist in the form of the so-called “physical PE” if the enterprise has effective power over the place of business where the remote employee creates the product to be delivered to the client. Alternatively, in the form of a “services PE”, remote employee is furnishing a service, for an extended period of time, from their host state to a client situated in another state; or an “agency PE” if that employee concludes contracts on behalf of their employer. However, by application of a series of scenarios, it is submitted that the host state can only, in very limited circumstances tax the employer. Because of the increased and continuous mobility of a remote employee, a physical PE will not be created because a physical PE requires permanence and geographical and commercial coherency. A services PE will not be created because it requires that the services relate to the “same project or connected projects” which creates complex interpretive issues for tax authorities. Moreover, the services PE's “duration” test allows for the avoidance of a services PE: a foreign enterprise can generate substantial revenue due to the services rendered by an employee in another state within a week without creating a taxable presence. An agency PE's limited application to the conclusion of contracts neglects the fact that the source of the profits, the work which a foreign enterprise does to earn the income flowing from the conclusion of the contracts, is done by an employee who may not be present when the contract is concluded. It is therefore submitted that the PE concept should be revisited to address these shortcomings, and the ATAF Model's services PE provision serves as a basis for a solution.